Electronic structure and magnetic properties of the CoFeMnZ (Z=As and Si) Heuslers by XAS, XMCD and MOKE: A DFT study. (March 2021) - Ilkhani, Mansoure; Yeganeh, Mahboubeh; Boochani, Arash; Yari, Arash
Highlights: Electronic, Magnetic andd MOKE properties Heusler alloys of CoFeMnZ (Z = Si, AS) were investigated by DFT. The calculated magnetic moments obey Slater-Pauling rule. XAS and XMCD spectra of CoFeMnZ (Z = Si, AS) were calculated and compared. The origin of XMCD was explained by DOS. Abstract: The electronic and magnetic and magneto-optic properties of the Heusler alloys of CoFeMnSi and CoFeMnAs were investigated by density functional theory. The density of states and magnetic moments were analyzed for both compounds and their magnetic moments obey the Slater-Pauling rule. The X-ray absorption and X-ray magnetic circular dichroism spectra of the constituent transition metals of these Heusler compounds were investigated and the origin of the XMCD spectra in these Heusler compounds was also studied through their density of states. The MOKE studies revealed the highest magnitude of Kerr rotation of 0.21° and 0.12° for CoFeMnAs and CoFeMnSi, respectively.